Publisher's Note: Search for di-muon decays of a low-mass Higgs boson in radiative decays of the [upsilon](1S) - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2013)
DOI:https://doi.org/10.1103/PhysRevD.87.059903